Arithmetical books from the invention of printing to the present time being brief notices of a large number of works drawn up from actual inspection - De Morgan, Augustus 1806-1871 (Cambridge University Press, 2014)
In the preface to this work, mathematician Augustus De Morgan (1806–71) claims that 'The most worthless book of a bygone day is a record worthy of preservation.' His purpose in writing this catalogue, published in 1847, was to provide an accurate record of the early history of publishing on arithmetic, but describing only those books which he had examined himself. He surveyed the library of the Royal Society, works in the British Museum, the wares of specialist booksellers, and the private collections of himself and his friends to compile a chronological list of books from 1491 to 1846 (the final book being a work of his own), giving bibliographical details, a description of the contents, and sometimes comments on the mathematics on display. De Morgan's Formal Logic and a Memoir of Augustus De Morgan by his widow are also reissued in the Cambridge Library Collection
Originally published in London by Taylor and Walton in 1847. - Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Arithmetic / Bibliography; Arithmetik; Bibliografie